Comparison of the Neodymium-doped Yttrium Aluminum Garnet Capsulotomy Rate with Viscoimplantation and the Hydroimplantation Intraocular Lens Technique - Oğurel, Tevfik (Korean J Ophthalmol, 2019)
PURPOSE: To investigate the rate of neodymium-doped yttrium aluminum garnet (Nd:YAG) laser capsulotomy in the hydroimplantation intraocular lens (IOL) technique. METHODS: This retrospective study was comprised of 6,192 eyes in 3,790 patients who underwent surgery from January 2013 to September 2017 and then were followed up for at least 1 year. The eyes of these patients were divided into two groups: either viscoimplantation or hydroimplantation. The follow-up examinations were carried out on the 1st day, 4th day, 1st month, and 3 months to 1 year postoperatively. The Nd:YAG capsulotomy rates were evaluated by the different IOL implantation techniques and IOL materials. RESULTS: The mean follow-up duration of the patients was in the viscoimplantation group 14.85 ± 2.43 and 15.05 ± 1.93 months in the hydroimplantation group. The Nd:YAG capsulotomy rate was significantly lower in the hydroimplantation group compared with the viscoimplantation group for the entire hydrophilic IOL model (p < 0.001). In addition, the Nd:YAG rate was lower in the hydroimplantation group that used a hydrophilic IOL than it was in the viscoimplantation group, which used a hydrophobic IOL. CONCLUSIONS: The hydroimplantation technique reduced the Nd:YAG capsulotomy rate.